A Nested Case-Control Study On Predictors Of Tuberculosis Relapse, Compliance And Cost Evaluation In Urban Areas Of Yemen - Anaam, Mohammed Saif Abdulhafedh (2013)
Tuberculosis (TB) is considered to be one of the major public health problems in Yemen. It is estimated that TB is the fourth cause of death based on hospitals statistics. Relapse of TB and patients’ non-compliance are serious problems leading to several complications. The present study was aimed to examine the influence of different factors on relapse of TB and patients’ compliance as well as to estimate the economic burden as consequences of relapse. The study design was a nested case control study that included 814 new smear positive pulmonary TB patients registered during a one year period (01-07-2007/31-06-2008) in ten governorates of Yemen. Data collection included two main phases; interviewing the participants at the end of intensive phase and reviewing their medical cards and TB registers at the end of the treatment. Factors investigated on relapse were demographic, socioeconomic, treatment and disease-related factors as well as factors evaluated after 2-3 months of treatment, and compliance with anti-TB therapy, while the factors investigated on compliance were demographic and socioeconomic factors as well as patients’ knowledge on TB, health education at health centre and adverse reactions of anti-TB drugs. A direct cost of relapse from government perspective was also evaluated. Student T-test and Mann-Whitney U test were used at alpha level of 0.05. Multiple logistic regression was employed to determine independently associated factors with relapse and patients’ non-compliance. The descriptive analysis in this study showed that 90% of respondents were at their most economically productive age (15-54 years old). Forty four relapse and 133 non-compliant cases were identified during the follow-up period. Multiple logistic regression analysis showed that the employment status (OR 3.93, 95% CI 1.41, 10.99), number of cigarettes smoked per day (OR 11.76, 95% CI 1.55, 89.11), presence of cavitations (OR 4.67, 95% CI 1.86, 11.70), weight loss (OR 8.11, 95% CI 3.10, 21.39), adherence in continuous phase (OR 17.94, 95% CI 1.69, 190.64), diabetes (OR 14.67, 95% CI 3.57, 60.20) and compliance (OR 3.73, 95% CI 1.39, 9.99) were significantly associated with TB relapse. While literacy (OR 1.87, 95% CI 1.08,3.25), employment status (OR 2.19, 95% CI 1.26,3.80), travelling time (OR 1.03, 95% CI 1.01,1.04), waiting time (OR 1.05, 95% CI 1.03,1.06), living status (OR 6.72, 95% CI 1.99,22.63), family support (OR 4.05, 95% CI 1.17,14.04), stigma (OR 1.75, 95% CI 1.06,2.89), Qat-chewing habit (OR 3.26, 95% CI 1.89,5.60) and patients’ knowledge on TB (OR 0.84, 95% CI 0.70,0.99) were risk factors for non-compliance.